2018
DOI: 10.1016/j.agee.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Can productivity and profitability be enhanced in intensively managed cereal systems while reducing the environmental footprint of production? Assessing sustainable intensification options in the breadbasket of India

Abstract: HighlightsHigher cereal productivity can be achieved with lower environmental footprint through conservation agriculture.Wheat productivity and profitability can be increased by zero-tillage and early sowing.Kharif maize appears to be a suitable and profitable alternative to rice in northwest India.Productivity and resource efficiency of transplanted rice can be improved by BMPs.Directly sown rice has potential to save water, energy and global warming potential compared to transplanted rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 52 publications
8
135
3
2
Order By: Relevance
“…Higher CWI under RT and CT practices was probably due to greater porosity created by tillage within the plowed layer and lower soil bulk density (as discussed in preceding sections) [59][60][61]. Higher CWI under RT practice could also be attributed to incorporation of crop residue in top 0-15 cm soil depth, which leads better soil porosity and aggregation formation [13,62]. Unlike the present study, other studies reported higher CWI under NT practice with residue retention as compared to CT practice.…”
Section: Cumulative Water Infiltrationcontrasting
confidence: 47%
“…Higher CWI under RT and CT practices was probably due to greater porosity created by tillage within the plowed layer and lower soil bulk density (as discussed in preceding sections) [59][60][61]. Higher CWI under RT practice could also be attributed to incorporation of crop residue in top 0-15 cm soil depth, which leads better soil porosity and aggregation formation [13,62]. Unlike the present study, other studies reported higher CWI under NT practice with residue retention as compared to CT practice.…”
Section: Cumulative Water Infiltrationcontrasting
confidence: 47%
“…The yield gains frequently observed in dry climates are commonly attributed to the improvements in soil water storage under CA (Halvorson et al, 2000;Eskandari, 2004, 2006;Li et al, 2007;Radford and and Thornton, 2011;Araya et al, 2012;Soane et al, 2012;Steward et al, 2018;Garcia-Palacios et al, 2019;Page et al, 2019). The possibility for early planting is also greater in CA systems due to the reduced land preparation requirements, which may result in more efficient use of rainfall and reduced risk of crop failure due to terminal heat stress (Kumar et al, 2018;Devkota et al, 2019). In hot regions, the lower soil temperatures under CA systems due to residue retention can also help improve plant growth and yield (Zhang et al, 2014;Steward et al, 2018).…”
Section: Impact On Yield Yield Stability and Farm Profitability Yieldmentioning
confidence: 99%
“…Period of study (yrs) and labor, and reduced water requirements (in irrigated systems) (Ngwira et al, 2012;Jat et al, 2014;Kumar et al, 2018;Devkota et al, 2019). Savings in fertilizer use, and in some instances reduced herbicide and insecticide costs, can also increase profitability (Kassam et al, 2009;LaCanne and Lundgren, 2018).…”
Section: Locationmentioning
confidence: 99%
“…A major advantage of ZT technology in wheat is that it facilitates early planting by reducing the turnaround period by reducing land preparation time because of directly drilling in ZT conditions. Early wheat planting has demonstrated a positive impact on wheat yield by mitigating the negative effect of terminal heat stress (Kumar et al 2018, CSISA 2015. These results suggest that ZT provides resilience in the changing climate change conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work shows that ZT directseeded rice (ZTDSR) is not yet fully ready for its wide-scale dissemination at farmer's field until weed management issues are resolved. DSR followed by ZT wheat (ZTW) has the potential to increase the system productivity with lower environmental footprint (Kumar et al 2018, Laik et al 2014, Bhushan et al 2007. There is no technological difficulty in introducing ZT DSR followed by ZT wheat as part of full-conservation agriculture (full-CA) as this is economically and environmentally more attractive.…”
Section: Introductionmentioning
confidence: 99%